Corpus creation and initial SMT experiments between Spanish and Shipibo-Konibo - Galarreta, A.-P.; Sasieta, A.; Oncevay, A. (Incoma, 2017)
In this paper, we present the first attempts to develop a machine translation (MT) system between Spanish and Shipibo-konibo (es-shp). There are very few digital texts written in Shipibo-konibo and even less bilingual texts that can be aligned, hence we had to create a parallel corpus using both bilingual and monolingual texts. We will describe how this corpus was made, as well as the process we followed to improve the quality of the sentences used to build a statistical MT model or SMT. The results obtained surpassed the baseline proposed (dictionary based) and made a promising result for further development considering the size of corpus used. Finally, it is expected that this MT system can be reinforced with the use of additional linguistic rules and automatic language processing functions that are being implemented.
Keywords: Computer science; Machine translation; Natural language processing; Artificial intelligence; Baseline (sea); Machine translation system; Process (computing); Quality (philosophy); Text corpus; Programming language; https://purl.org/pe-repo/ocde/ford#1.02.01